1981
DOI: 10.1111/j.1365-2222.1981.tb01602.x
|View full text |Cite
|
Sign up to set email alerts
|

Eczema and infant diet

Abstract: The relationship between parental atopy, breast-feeding, early solid food diet and the rate of eczema was studied in a birth cohort of 2-year-old children. Rates of eczema varied significantly with parental atopy and solid feeding: children of aiopic parents given solid food during the first 4 months had over two-and-a-half times the rate of eczema of children not given solid food and who had non-atopic parents. Further, rates of eczema increased in almosl direct proportion lo the number of diflerent types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
3
3

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(102 citation statements)
references
References 19 publications
3
93
3
3
Order By: Relevance
“…Unlike the previous study by Fergusson et al, 11 this study found no significant association between the numbers of food types introduced before age 4 months and eczema.…”
Section: Studies Finding No Association Between Early Introduction Ofcontrasting
confidence: 84%
“…Unlike the previous study by Fergusson et al, 11 this study found no significant association between the numbers of food types introduced before age 4 months and eczema.…”
Section: Studies Finding No Association Between Early Introduction Ofcontrasting
confidence: 84%
“…More recent data (1981) from New Zealand, however, showed an incidence of 12% in 2 year old infants with no atopic family history (compared with 18% in our study). 24 Interestingly, though, this study demonstrated that in the subgroup of children with a positive atopic family history, the incidence of eczema (24%) was similar to ours (25%). Further study, comparing preterm and term infants using the same data collection procedure, would be needed to examine the possibility raised here, that preterm infants are a high risk group for eczema.…”
Section: Discussionsupporting
confidence: 82%
“…The favorable effect may be moderate and limited to, or more conspicuous in, infants at high risk of atopy. Also, other interventions may be needed, such as combining breastfeeding with avoidance of solid food for the fi rst 4 months for maximal benefi t [ 26 ].…”
Section: Breastfeedingmentioning
confidence: 99%